The Ghidra book : the definitive guide - Eagle, Chris; Nance, Kara (No Starch Press, 2020)
A guide to using the Ghidra software reverse engineering tool suite. The ability to analyze software with a disassembler is a crucial reverse engineering skill and one of the core competencies expected of malware analysts and software security researchers. Ghidra is one of the world's most capable disassemblers, and it's the only one that includes an environment for collaborative reverse engineering. Ghidra is also a comprehensive open source tool suite and a powerful alternative to the commercial competitors that come with a hefty price tag and steep learning curve. The Ghidra Book teaches you how to use Ghidra to answer the hardest problems about software behavior. It is a tutorial about Ghidra's features that includes instructions on how to use and modify the open source software to make it meet the needs of any individual or organization. The book begins with some background on the reverse engineering process. You are then introduced to important Ghidra features together with examples showing how to customize and augment the suite. You'll learn how to: Navigate a disassembly Use Ghidra's built-in decompiler to expedite analysis Analyze obfuscated binaries Extend Ghidra to recognize new data types Build new Ghidra analyzers Build new Ghidra loaders Add support for new processors and instruction sets Script Ghidra tasks to automate workflows Set up and use a collaborative reverse engineering environment By the end of the book, you will have learned how to use Ghidra efficiently and maximize its effectiveness.